Mark Thurner y Jorge Cañizares-Esguerra (editores), The Invention of Humboldt: On the Geopolitics of Knowledge - Susana V. García (Prismas)
Mark Thurner y Jorge Cañizares-Esguerra (editores), The Invention of Humboldt: On the Geopolitics of Knowledge